Strategies to Produce Warrior Ulema through Islamic Education - Makhreza Ahmad Faisal (International Journal of Global Sustainable Research, 2023)
Scholars are the heirs of the prophets. Without righteous and righteous scholars, it is impossible for the existence of Islam to continue. Therefore, the presence of scholars needs to continue regeneration efforts. This study aims to describe how Islamic education strategies are able to produce scholars with warrior characters. The collected data sources are then analyzed by qualitative descriptive methods with a historical approach. As a result, the application of Islamic education taught by the Prophet SAW has proven successful in producing warrior scholars. Because historically, the Prophet Muhammad through the educational strategy he brought has been able to produce scholars who successor the Prophets, ranging from khulafaur rashidin, tabi'in to contemporary scholars.